EFFECTIVENESS OF COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) STRATEGIES IN WRITING ARGUMENTATION CORRECTIONS CLASS X SMA STATE 1 BUA PONRANG (KEEFEKTIFAN STRATEGI COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) DALAM MENULIS KARANGAN ARGUMENTASI KELAS X SMA NEGERI 1 BUA PONRANG) - Musyawir, Musyawir; Yulismayanti, Yulismayanti (Universitas PGRI Sumatera Barat, 2018)
The reseach aims to describe the effectiveness of cooperative integrated reading and composition strategy in writing argumentation composition learning to class X students at SMAN Bua Ponrang. The reseach is experiment research which employs true experiment design. Thesubject of the research were class X students at SMAN 1 Bua Ponrang of academic years o2016/2017 with the total of 245 students. The sample of the research were taken by using randomtechnique and class X4 was chosen as the experiment class and class X6 was chosen as the controclass. The data obtained were analysed by using descriptive and inferensial statistics analysis witt-test. The result of the research reveal that there is significant difference between writingargumentation composition learning using CIRC strategy and writing argumentation compositionlearning without using CIRC strategy, and abilities and writing argumentation composition betweethe group which was given the treatment is effective to be used as a strategy in writingargumentation composition learning to class X SMAN 1 Bua Ponrang. The effectiveness of writing argumentation composition is showed by t-test in initial an final test of the experiment and controlthe experiment group wich obtained t count 5.159 with db 31 and p score 0.000. The p score ismaller that the significant level 5% which stated that learning is effective. The control class theinitial and final test obtained it count 5.697 with db 31 and p score 0.000. The p score is smallethat significant level 5%. Which stated that learning in the experiment class is effective.